Metodología de cálculo para una minicentral hidroeléctrica en el sector de "San Lucas". - Ríos Toro, Eduardo Xavier. (2005)
The present diploma work is structured in three chapters. In the first one it is approached the fundamental theoretical aspects of the hydroelectric main components of the mini-central ones, in the chapter two the calculation methodology is shown of what constitutes the hydroelectric power station with the height and existent flow, a proposal for the selection of a Pelton Turbine using the unitary parameters, as well as the previous dimension of the same one, and in the chapter three an analysis is exposed on the assembly aspects, operation and technician-economic appraisement besides the environmental impact that will have the application of this project in our environment.